Relation between University Geographies and Syllabuses for Geography Instruction in General Secondary Schools in Slovenia - Konečnik Kotnik, Eva; Kolnik, Karmen (Journal of Geography Education, 2012)
In this empirically based study the syllabuses of geography instruction are evaluated by academics at the university level. They had to evaluate the objectives and terminology of physical geography, human geography and regional geography in the syllabus of geography instruction in secondary schools in Slovenia. The terminology as well as the objectives for human geography and in a lesser way for physical geography was quite criticized. The evaluation of the regional geography was ambiguous.
Keywords: evaluation, teaching geography, Slovenia, university geography